Österreichischer Sachstandsbericht Klimawandel 2014 - Kromp-Kolb, Helga (Verlag der Österreichischen Akademie der Wissenschaften, 2014)
The AAR14 is the first Assessment Report on climate Change in Austria assessing the Impact of climate change and the Needs and possibilities of mitigation and Adaptation. This three-volume Report, developed through a multiple peer-Review process including stakeholder participation, presents a coherent assessment of scientific knowledge about climate and makes it accessible for both decision-makers and the General public. Approximately 240 scientists from 50 institutions have participated in this national Assessment Report